Creating Kabuki Plays Context for Kezairoku, "Valuable Notes on Playwriting" - Saltzman-Li, Katherine (Brill, 2010)
This volume makes available for the first time a complete translation in English of a key text for our understanding of Kabuki, viz. Kezairoku, Sakusha Shikihô (Valuable Notes on Playwriting, A Playwrights' Methodology, written 1801), being the only extant treatise fully devoted to the subject of Kabuki playwriting. At the hand of this vital text, the author addresses the history, methodology, and practitioners of Kabuki playwriting of the Edo Period (1603-1867.) The reader will find a critical examination of Kezairoku, and discussions regarding the connections between the Kabuki and literary worlds of Edo Japan, and between playwriting and the oral arts. The availability of the entire Kezairoku in English, together with a full contextualization of its teachings and meanings, offers a volume of great significance to both Japan and theatre scholars.